Prevalence and Awareness of Diabetic Retinopathy in diabetes Patients Attending Ayurveda Hospital, Kirtipur - Parajuli, Sadhana (Curriculum Development Journal, 2025)
Diabetic retinopathy understood in Ayurveda as Madhumehajanya Timira disorder arising from Prameha (diabetes) is the most prevalent micro vascular complication associated with diabetes mellitus and leading cause of blindness. The main objective of the study was to find the awareness of diabetic retinopathy and blindness due to diabetic retinopathy among diabetes patients visiting Ayurveda Hospital Kirtipur. It is survey study; patients diagnosed with diabetes were included for study and interview questionnaires were used to collect data from November 2020 to December 2020. Approximately one third of the respondents were in the late middle age to early old age group. More than sixty percentage were male patients than the females. Three- fifth had attained education up to the school level, and thirty eight percent identified as Brahmins. Nearly all respondents were under medication for diabetes mellitus, with nearly fifty percent having taken medication for more than ten years. More than three- fifth of the participants were aware of diabetic retinopathy, and more than fifty percent reported attending regular checkups. More than one- half of respondents were aware of Diabetes mellitus may cause for blindness and more than one - third were not aware about untreated Diabetes mellitus may cause blindness in future. More than one - half had received information through doctors during hospital visit about Diabetic retinopathy blindness. Mostly fifty percent had history of Diabetic Retinopathy for six month and nearly two- fifth had history for 1-2 years. There was a relationship observed between diabetic retinopathy and the duration of diabetes mellitus, with a p-value of 0.09. Although this does not meet the conventional threshold for statistical significance (p < 0.05), it suggests a potential association that may warrant further investigation.